Dynamic Modeling of Autonomous Wind–diesel system with Fixed-speed Wind Turbine - Najafi Hamid Reza; Dastyar Farshad (International Journal of Applied Power Engineering (IJAPE), 2012)
Wind turbines have often connected to small power systems, operating in parallel to diesel generators, as is typically the case in autonomous wind–diesel installations or small island systems with high wind potential. Hence, the modeling and analysis of the dynamic behavior of wind–diesel power systems in presence of wind power will be important. In this paper, the system under study is modeled by a set of dynamic and algebraic equations (DAE). Dynamic behavior of a wind-diesel system is investigated by the proposed dynamic model. Wind-diesel system consists of wind turbines that are connected to synchronous diesel generator via short transmission line with local load. Dynamic stability of autonomous wind–diesel systems are discussed with emphasis on the eigenvalue analysis and the effective parameters on system stability. In this regards, saddle node bifurcation and hopf bifurcation are also investigated.